Adipose-derived stem cells in cartilage regeneration: current perspectives. (October 2016) - Bielli, Alessandra; Scioli, Maria Giovanna; Gentile, Pietro; Cervelli, Valerio; Orlandi, Augusto
Repair of cartilage injuries represents a musculoskeletal medicine criticism because of the poor ability to self-renewal of adult cartilage. Therefore, research focuses on developing new regenerative strategies combining chondrocytes or stem cells, scaffolds and growth factors. Because of the low proliferation capability of explanted chondrocytes, new chondrogenesis models, employing human adipose-derived stem cells (ASCs), have been investigated. ASCs are readily accessible with no morbidity and display the capability to differentiate into several cell lineages, including the spontaneous chondrogenic differentiation when entrapped in collagen gel scaffolds. Recent studies also defined some biomolecular mechanisms involved in ASC chondrogenesis in vitro, and their regenerative properties in bioengineered scaffolds and in the presence of growth factors. However, further investigations are required to validate these exciting preclinical results for the application of bioenginereed ASCs in the clinical practice.